A metal-free 2D layered organic ammonium halide framework realizing full-color persistent room-temperature phosphorescence. Issue 43 (21st October 2021) - Feng, Shangwei; Huang, Qiuqin; Yang, Shuming; Lin, Zhenghuan; Ling, Qidan
Abstract : A kind of metal-free organic ammonium halides characterized by a unique 2D layered structure show colorful ultralong phosphorescence. Phosphorescent quantum yield (up to 19%) and lifetime (up to 1.7 s) can be tuned by doping with different phosphors. Abstract : Organic–inorganic hybrid metal halides have attracted intensive attention because of their unique electronic structure and solution processability. They have a rigid micro/nano-structure and heavy atom effect, which has obvious advantages in promoting organic room temperature phosphorescence (RTP). However, the toxicity of heavy metals has limited their further development. Herein, two metal-free 2D layered ammonium halides, homopiperonylammonium bromide and chloride (HLB and HLC), are described for the first time. Their layered structure consists of rigid inorganic ammonium halide laminates and neatly stacked organic layers. The rigid laminates and external heavy atom effect of halogen atoms make HLB and HLC produce green RTP. When phosphor guests with different triplet energies are doped into HLB, HLC, or phenylethylamine salt hosts, effective full-color and even white ultra-long RTP with phosphorescence quantum yield up to 18.7% and lifetime up to 1.7 s is realized through energy transfer between the host and guest. Due to the simple solution synthesis, 10 g-level doped layered organic ammonium halides with the same phosphorescence properties can be easily obtained. The information ink based on these doped halides and non-toxic ethanol solvent can form various patterns on filter paper. The fluorescence and phosphorescence of these patterns are sensitive to the excitation wavelength and acid–base vapor. Consequently, they can be applied to multiple complex anti-counterfeiting and fluorescence/phosphorescence dual-mode chemical sensors.